Phraseological structure of a ritual discourse of Vostochnoslobozhansky diаlect (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article is dedicated to the phraseology studing of rituals of Vostochnoslobozhansky dialect. The importance of ethnolinguistic approach during the research of ritual phraseological units semantics is emphasized.
Keywords: etnolingvistika; ceremonial discours; ceremonial phraseology; ceremonial phraseological unit; semantics